2013
DOI: 10.1021/ml400232p
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Multitarget Interactions to Reduce Opiate Withdrawal Syndrome and Psychiatric Comorbidity

Abstract: Opioid addiction is often characterized as a chronic relapsing condition due to the severe somatic and behavioral signs, associated with depressive disorders, triggered by opiate withdrawal. Since prolonged abstinence remains a major challenge, our interest has been addressed to such objective. Exploring multitarget interactions, the present investigation suggests that 3 or its (S)-enantiomer and 4, endowed with effective α 2C -AR agonism/α 2A -AR antagonism/5-HT 1A -R agonism, or 7 and 9−11 producing efficaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
(77 reference statements)
0
18
0
1
Order By: Relevance
“…In particular, the combined I 1 -/I 2 -IBS/α 2 -ARs interaction appeared more favorable, as demonstrated by the higher efficacy displayed by 9 both in contrasting and preventing morphine withdrawal. Moreover, such a combination also appeared more favorable than that produced by 2 (I 2 -IBS/α 2 -ARs), already evaluated in the same assays 18 (see Table S2). Therefore, 9 might be considered a promising tool useful in managing opioid addiction, potentially lacking in sedative and hypotensive side effects, due to its α 2A -AR antagonist profile.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 65%
“…In particular, the combined I 1 -/I 2 -IBS/α 2 -ARs interaction appeared more favorable, as demonstrated by the higher efficacy displayed by 9 both in contrasting and preventing morphine withdrawal. Moreover, such a combination also appeared more favorable than that produced by 2 (I 2 -IBS/α 2 -ARs), already evaluated in the same assays 18 (see Table S2). Therefore, 9 might be considered a promising tool useful in managing opioid addiction, potentially lacking in sedative and hypotensive side effects, due to its α 2A -AR antagonist profile.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 65%
“…3 Using this molecular core, over many years we have developed several ligands directed to different biological systems including α 2 -adrenergic and 5-HT 1A -serotoninergic receptors and imidazoline binding sites (I-IBS). Some of these compounds showed interesting in vivo pharmacological properties such as antidepressant 4 and antinociceptive 5 activities, enhancement of morphine-induced analgesia, 6 decrease of both acquisition and expression of morphine tolerance and dependence, 7 as well as hyperanxiety-like behavior after alcohol intoxication, 8 hypotensive and bradicardic effects. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Our experience also highlighted that the bridge (X) and the aromatic area (Ar) forming the substituent in the 2‐position of the imidazoline nucleus display different functions. Indeed, minor chemical modification of the bridge determines preferential or multitarget recognition, whereas modification in the aromatic region is generally responsible for the functional behavior of the ligand …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the beneficial effects of 1 as well as 2 and 3 on morphine dependence proved to be associated, at the same low dose, to a significant antidepressant effect. Experiments performed in the presence of the α 2 ‐AR antagonist yohimbine and the serotonin 5‐HT 1A receptor (5‐HT 1A ‐R) antagonist WAY100135 suggested that not only α 2C ‐AR but also 5‐HT 1A ‐R activation was involved in the observed antidepressant‐like activity . In addition, 1 reduced hyperanxiety‐like behavior after alcohol intoxication at the same low dose .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation